GROYS, B. (2022). Filosofía del cuidado. Buenos Aires: Caja Negra. - Altamira Camacho, Ramiro; Herrera Justicia, Sonia (Daimon Revista Internacional de Filosofia, 2024)
Reseña de GROYS, B. (2022). Filosofía del cuidado. Buenos Aires: Caja Negra.